TRFs and tiRNAs sequence in acute rejection for vascularized composite allotransplantation - Fang, Yuan; Li, Haibo; Chen, Jingting; Xiong, Yao; Li, Xu; Sun, Binbin; Li, Shengli; Zhou, Jianda; Wang, Shoubao (Scientific data, 2022)
Illumina tRFs & tiRNAs-seq analysis was used to characterize the whole transcriptomes of acute rejection caused by vascularized composite allotransplantation (VCA). tRFs & tiRNAs-seq information for muscle samples with VCA was obtained and compared with similar information for same age- and sex-matched healthy control subjects. The expression of 16 tRFs and tiRNAs, including 5 up-regulated target genes and 11 down-regulated target genes, were significantly different. According to bioinformatics analysis and reverse transcription quantitative polymerase chain reaction, we speculate that tiRNA-1-34-Glu-CTC-1 plays an important role in VCA-induced acute rejection by regulating the CACNA1D gene in the MAPK signaling pathway The findings provide the whole-transcriptome signatures of acute rejection for VCA, allowing further exploration of gene expression patterns/signatures associated with the various clinical symptoms of acute rejection for VCA. Measurement(s) gene expression Technology Type(s) RNA sequence Factor Type(s) RNA Sample Characteristic - Organism rn6 Sample Characteristic - Location China